Live Search for Mobile: Web Services by Voice on the Cellphone - Acero, Alex; Bernstein, N.; Chambers, R.; Ju, Y. C.; Li, Xiao; Nguyen, Patrick; Scholz, O.; Zweig, Geoffrey (Proc. of the Int. Conf. on Acoustics, Speech, and Signal Processing, 2008)
Live Search for Mobile is a cellphone application that allows users to interact with web-based information portals. Currently the implementation is focused on information related to local businesses: their phone numbers and addresses, directions, reviews, maps of the surrounding area, and traffic. This paper describes a speech-recognition interface which was recently developed for the application, which allows the users to interact by voice. The paper presents the overall architecture, the user interface, the design and implementation of the speech recognition grammars, and initial performance results indicating that for sentence level utterance recognition we achieve 60 to 65% of human capability.